2011
DOI: 10.1111/j.1551-2916.2011.04674.x
|View full text |Cite
|
Sign up to set email alerts
|

Onset Plastic Deformation and Cracking Behavior of Silicon Carbide under Contact Load at Room Temperature

Abstract: The room temperature onset plastic deformation and crack behavior of 3C-SiC under contact load were investigated using nanoindentation and transmission electron microscopy (TEM). During loading, abrupt bursts or pop-in in the load-displacement curves was observed at a depth of~60 nm. The 3C-SiC deforms elastically before the pop-in depth, but exhibits a plastic-elastic behavior after that. TEM observations reveal that the shear slip is the predominant deformation mechanism in 3C-SiC during indentation. The cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…This analysis is based on evaluation of the maximum shear stress and maximum tensile strength underneath the indenter during the process of nanoindentation. The maximum shear stress underneath the indenter can be found out using the following equation [14]:…”
Section: : P-h Plots For Indentations Made On Single Crystal 4h-sic Amentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis is based on evaluation of the maximum shear stress and maximum tensile strength underneath the indenter during the process of nanoindentation. The maximum shear stress underneath the indenter can be found out using the following equation [14]:…”
Section: : P-h Plots For Indentations Made On Single Crystal 4h-sic Amentioning
confidence: 99%
“…The tensile stresses and cleavage strength of 4H-SiC were obtained using the following equation [14]:…”
Section: : P-h Plots For Indentations Made On Single Crystal 4h-sic Amentioning
confidence: 99%
See 1 more Smart Citation
“…In nanoindentation, the elastic response of a material is assessed within a small measurement volume that is subject to an extreme hydrostatic stress. Thus, this approach differs substantially from macroscopic bending testing techniques, since shear bands with associated dislocations and microcracks form to accommodate the plastic deformation [27,28,45]. With an increasing concentration of such defects in the volume beneath the indenter at higher temperatures the materials' elastic response is likely to be affected.…”
Section: Impact Of Porositymentioning
confidence: 99%
“…Earlier studies have shown that even at room temperature, the initial plastic deformation in SiC during nanoindentation is related to dislocation activity [27]. With the small curvature radius of the indenter tip a strong hydrostatic stress field is induced in which the critical shear strength is exceeded before the tensile stresses reach the cleavage strength [28]. Considering that subsequent SEM imaging showed cracking around the indent imprints regardless of the measurement temperature, it could be concluded that for the temperature range investigated here nanoindentation measurements induced plastic deformation by dislocation activity as well as fracture.…”
Section: Variation In Grain Sizementioning
confidence: 99%